The effect of giving lemon aromatherapy to first trimester pregnant women with emesis gravidarum at PMB klinik Santa Elisabeth Kefamenanu - Fitriyaningsih, Fitriyaningsih (Journal Health of Indonesian, 2024)
Nausea and vomiting in pregnancy is commonly called morning sickness, experienced by about 70-80% of pregnant women and is a phenomenon that often occurs at 5-12 weeks of pregnancy. Lemon essential oil (Citrus Lemon) is one of the herbal oils that is considered the safest medicine in pregnancy. The purpose of this research is to determine the effect of giving lemon aromatherapy to first trimester pregnant women with emesis gravidarum. This study uses a quasy experimental design or pseudo-experiment method using a pretest and posttest design with control. In this design before the treatment is given, the sample is first given a pretest (initial test) and after the experiment the sample is given a posttest (final test). This design is used in accordance with the objectives to be achieved, namely to determine the effect of lemon aromatherapy on the frequency of emesis in first trimester pregnant women. The results of the analysis show the effect of giving lemon aromatherapy to reduce nausea and vomiting in pregnant women at the Santa Elisabeth Kefamenanu Clinic, where the ρ value = 0.000 (<0.05) is obtained. As well as producing the conclusion that there is a relationship between giving lemon aroma therapy to pregnant women in the first trimester.